Lectotypification of Psyllocarpus schwackei (Spermacoceae, Rubiaceae) - Carmo, João A.m.; Scalon, Viviane R.; Calió, Maria F.; Simões, André O. (Phytotaxa, 2017)
Psyllocarpus schwackei was described by Schumann (1898: 18), for which he cited a single collection, “in Brasiliae civitate Minas Geraes, locis arenosis in Serra do Cipo: Schwacke n, 8089, floret Aprili”. In a taxonomic revision of the genus, Kirkbride (1979) stated that the material studied by Schumann at the Botanical Museum in Berlin had been destroyed during the Second World War (Hiepko 1987), and that he was unable to locate any duplicates of this collection. He consulted a photograph of the specimen available in the Field Museum of Natural History type photograph series, negative number 896. Therefore, based upon the original description of the species, the photograph he analysed, and his experience at the type locality, the Serra do Cipó, Minas Gerais state, Kirkbride (1979) selected as neotype the collection “Serra do Cipó, elev. ca. 1125 m, Anderson et al. 36254 (neotype US; isoneotypes NY, UB)”.